The effect of thermal cycles on the mechanical properties of fiber-metal laminates - da Costa, Adriana A.; da Silva, Danielle F. N. R.; Travessa, Dilermando N.; Botelho, Edson Cocchieri [UNESP] (Elsevier B.V., 2012)
The effect of thermal-shock cycles on the mechanical properties of fiber-metal laminates (FMLs) has been evaluated. FML plates were composed by two AA2024 Al sheets (1.6 mm thick) and one composite ply formed by two layers of unidirectional glass fiber epoxy prepreg and two layers of epoxy adhesive tape of glass fiber reinforced epoxy adhesive. The set was manufactured by hand layup and typical vacuum bag technique. The curing cycle was in autoclave at 125 +/- 5 degrees C for 90 min and an autoclave pressure of 400 kPa. FML coupons taken from the manufactured plate were submitted to temperature variations between -50 and +80 degrees C, with a fast transition between these temperatures. Tensile and interlaminar shear strength were evaluated on samples after 1000 and 2000 cycles, and compared to nonexposed samples. 2000 Cycles corresponds to typical C Check interval for commercial aircraft maintenance programs. It was observed that the thermal-shock cycles did not result in significant microstructural changes on the FML, particularly on the composite ply. Similarly, no appreciable effect on the mechanical properties of FML was observed by the thermal-shock cycles. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Fiber-metal laminates; Thermal cycling; Tensile strength; Interlaminar shear strength